(untitled) (Costos y Gestión, 2024)
The research presents the results of the application of the Activity Based Costing (ABC) methodology in a dental clinic located in the city of Quito. The objective was to analyze the impact generated by the application of this methodology versus the traditional cost system used by the company, on the gross profitability of 41 dental procedures. A descriptive case study approach was carried out using data col¬lection techniques such as semi-structured interviews and direct observation. The article seeks to be a guide for other clinics in the area of oral health to distribute indirect costs (items that are difficult to quan¬tify) based on a methodology supported by extensive literature. The results show that, under traditional costing, 20 procedures are not profitable, this considering that the indirect costs are calculated based on a percentage allocation that is unknown how they were obtained, on the other hand, through ABC it is shown that 8 procedures are not profitable and are being subsidized, since the greater the number of procedures offered, the indirect costs decrease, therefore, they tend to generate profitability.